Development of a ratiometric fluorescent probe with a large emission shift for imaging ONOO− in live cells and zebrafish. (February 2020) - Jia, Pan; Zhuang, Zihan; Liu, Caiyun; Wang, Zuokai; Duan, Qingxia; Li, Zilu; Zhu, Hanchuang; Zhang, Fenfen; Sheng, Wenlong; Zhu, Baocun
Abstract: Developing a reliable tool for monitoring peroxynitrite (ONOO − ) in the complex organisms is critical to uncover its detailed cellular functions in numerous physiological and pathological processes. Thus, a novel ratiometric fluorescent probe was reasonably designed for ONOO −, in which the rhodol-HBT conjugate dye was chosen as a fluorophore, and hydrazine moiety was adopted as recognition receptor of ONOO − . The probe exhibited outstanding sensitivity, specificity, and a fast response towards ONOO − . More importantly, the probe with a large emission shift (Δλem = 127 nm) has been proven to be capable of tracking ONOO − with high resolution in live cells and zebrafish. This work provides a simple and reliable tool for detecting and imaging ONOO − in the living systems, and thus we anticipate that the designed probe could be used as a powerful imaging tool in unraveling biological functions of ONOO − . Graphical abstract: Image 1 Highlights: A new ratiometric fluorescent probe with a large emission shift for ONOO − was designed. The probe exhibited prominent selectivity towards ONOO − . The probe displayed an ultrafast response for ONOO − (within 10 s). The probe was used to the high-resolution imaging of ONOO − in live cells and zebrafish.